PECULIAR STATIONARY EUV WAVE FRONTS in the ERUPTION on 2011 MAY 11 - Chandra R.; Chen P.F.; Fulara A.; Srivastava A.K.; Uddin W. (My University, 2025)
We present and interpret the observations of extreme ultraviolet (EUV) waves associated with a filament eruption on 2011 May 11. The filament eruption also produces a small B-class two ribbon flare and a coronal mass ejection. The event is observed by the Solar Dynamic Observatory with high spatio-temporal resolution data recorded by the Atmospheric Imaging Assembly. As the filament erupts, we observe two types of EUV waves (slow and fast) propagating outwards. The faster EUV wave has a propagation velocity of ∼500 km s-1 and the slower EUV wave has an initial velocity of ∼120 km s-1. We report, for the first time, that not only does the slower EUV wave stop at a magnetic separatrix to form bright stationary fronts, but also the faster EUV wave transits a magnetic separatrix, leaving another stationary EUV front behind. © 2016. The American Astronomical Society. All rights reserved.